Refinements of Inequalities among Difference of Means. (4th October 2012) - Shi, Huan-Nan; Li, Da-Mao; Zhang, Jian
Abstract : In this paper, for the difference of famous means discussed by Taneja in 2005, we study the Schur-geometric convexity in (0, ∞) × (0, ∞) of the difference between them. Moreover some inequalities related to the difference of those means are obtained.